Comparative evaluation of carbon footprints between rice and potato food considering the characteristic of Chinese diet. (1st June 2020) - Xu, Zhongyue; Fu, Zhineng; Zhai, Zongyao; Yang, Xiaoke; Meng, Fanjing; Feng, Xin; Zhong, Jianlan; Dai, Yongwu; Xu, Weijun; Cheng, Jun-Hu; Zhang, Zhihang
Abstract: Rice and potato are Chinese traditional foods. In this research, carbon footprints (CFs) of rice-based (RBSF) and potato-based (PBSF) staple foods were investigated. A great number of studies related to food CFs are often concerned about agricultural cultivation. However, the predominant source stage was cooking for the boiled potato and processing for the mashed potato in this research, accounting for 58.8% and 71.6% of their total CF, respectively. To support effective policies that reduce carbon emissions, assessments of the product CFs at a wider system boundary are more reliable. In addition, the types showed significant impacts on the food CFs, as the CF value of late indica rice was about 1.7 times more than that of early indica rice with a similar processing level. Therefore, adjustment of rice planting proportion and area could reduce agricultural carbon emissions. Sensitivity analysis showed that appropriately increasing the cooking amount in a batch enhances environmental benefits. When the cooking amount was reduced from four portions to one portion, the CF value was increased by 30%–45% for the RBSB and 89.5% for the boiled potato. On the other hand, different functional units were employed to evaluate the food CFs. CF values per functional unit for a same type of food varied greatly depending on the functional unit applied. Nutrient density (ND) based functional unit is more suitable to exactly reveal the environmental impacts of foods. When the ND based functional unit was used, CF values of polished rice and mashed potato indicated strong unsustainability. The results in this study showed that boiled potato consumed as the staple food is beneficial from both environmental and nutritional viewpoints. However, PBSF prepared by potato powder was not an eco-friendly food choice. The strategy of developing potato as staple food deserves serious consideration by Chinese government. Highlights: Carbon footprints of food were evaluated based on the characteristic of Chinese diet. Assessments of product CFs at a wider system boundary are more reliable. Strategy of developing boiled potato as staple food is beneficial for environment. Potato food prepared by potato powder is not an eco-friendly food choice. The strategy of developing potato as staple food deserves serious consideration.